2020
DOI: 10.1111/jfs.12842
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and population analysis of Vibrio parahaemolyticus in retail aquatic products from the southern Fujian coast, China

Abstract: Vibrio parahaemolyticus is one of the most hazardous pathogens causing seafood-borne diseases in the southern Fujian coast, China. From June to October 2016, a total of 250 samples were collected from retail markets in the Xiamen, Quanzhou, and Zhangzhou regions. Seventy-seven V. parahaemolyticus isolates were identified using polymerase chain reaction (PCR). Then, molecular typing was performed using repetitive extragenic palindromic-PCR (REP-PCR). The distribution of seven virulence genes was detected by PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…parahaemolyticus was reported as 20.0% and 14.0% in short-necked clams (Paphia variegata) and white shrimps (Penaeus vannamei) from China, which is lower than our findings [111] . In contrast, oysters (Crassostrea gigas) sampled in Kang et al [113] showed a higher prevalence (85.5%) of the bacteria in their study.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…parahaemolyticus was reported as 20.0% and 14.0% in short-necked clams (Paphia variegata) and white shrimps (Penaeus vannamei) from China, which is lower than our findings [111] . In contrast, oysters (Crassostrea gigas) sampled in Kang et al [113] showed a higher prevalence (85.5%) of the bacteria in their study.…”
Section: Discussioncontrasting
confidence: 94%
“…There is a considerable amount of literature concerning V. parahaemolyticus in seafood from Asia. Despite the subtle variation in the methodologies employed, ultimately, most studies have consistently used the toxR-or tlh-PCR amplification technique, which allows accurate comparisons of findings to be made [90,[109][110][111][112][113] . The overall prevalence of V.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shellfish products were utilized to evaluate the reliability of the LAMP-LFD assays in natural food samples: 30 aquatic products (short-necked clam, n = 10; Asiatic hard clam, n = 10; razor clam, n = 10) were collected from 3 local retail markets in Zhangzhou, China. V. parahaemolyticus isolates were detected from natural food samples following the method described by Yuanqing [ 28 ]. Briefly, 25 g of each sample was homogenized with 225 ml alkaline peptone water (APW, Land Bridge Technology, China) containing 3% (w/v) NaCl, and homogenates were streaked onto TCBS agar plates and incubated at 37°C for 18-24 h. Green or blue green colonies were spread onto new TCBS plates for purification at 37°C for 18 h, and presumptive colonies were chosen for identification by Gram staining and biochemical tests (oxidase activity; halophilic test; urease test; citrate utilization test; decomposition test of sucrose, glucose and mannitol; 3% (w/v) NaCl triple sugar iron tests).…”
Section: Methodsmentioning
confidence: 99%